UPAYA PEMBENTUKAN KARAKTER PADA SISWA KELAS V MELALUI PENDIDIKAN KEAGAMAAN DI MI SALAFIYAH 02 TASIKMADU TAHUN PELAJARAN 2017/2018 - Taufik; Siti Nurjanah (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2018)
Religious education is expected to be able to produce good personality traits. A good child personality can be seen with his efforts in perfecting faith, piety, and noble character. Such noble character includes ethics, character, or morals as an embodiment of education. Based on the background of the problem, this research is expected to provide an answer to the problem formulation (1) What is the effort of character building in fifth grade children through religious education at MI Salafiyah 02 Tasikmadu? (2) How is the effectiveness of character building in grade V children through religious education at MI Salafiyah 02 Tasikmadu? (3) What are the inhibiting and supporting factors in character building in fifth grade children through religious education at Salafiyah 02 Tasikmadu MI ?. This research was conducted at Salafiyah 02 Tasikmadu MI by using qualitative research. Qualitative research is a method for understanding individuals that is done integratively and comprehensively in order to obtain a deep understanding of the individual and the problems he faces with the aim of the problem being solved and obtaining good self-development. The type of qualitative research used in this study is intended for children. In addition, the qualitative research approach is expected to reveal the situation and problems faced in the effort to shape character through religious education. The results of the research are the efforts carried out by researchers in this research are to shape the character of children through religious education by inviting children to carry out religious activities. For example prayers together, istighosah do'a before and after learning etc. These are all part of the efforts made by researchers to familiarize children with awareness to carry out religious activities. The effectiveness of religious education in forming characters in Salafiyah MI began to appear. Children who were initially lazy to carry out religious education activities are now starting to be active along with the formation of character that is carried out regularly every day. Religious education is very effective in shaping the character of a child that begins to fade with the times. With this study held, in Salafiyah MI 02 the Tasikmadu began to appear that character emerged with various religious education activities. The inhibiting factor of this research is that the area is not extensive, because the children are still alternating with other classes, lack of enthusiasm of children towards religious activities, besides that there are still children who like to joke when the activities take place. Supporting factors in forming educational activities are teachers at Salafiyah MI 02 Tasikmadu always follows the activities carried out, children who are starting to be enthusiastic about religious education activities always start when the activity takes place.